The Emergent Role of Local Government On Covid-19 Outbreak In Indonesia: A New State-Society Perspective - Helen Dian Fridayani; Jenn Jaw Soong (Journal of Governance, 2021)
This article is conducted to describe and analyze the local government in handling the Covid-19 outbreak. The spread of the coronavirus (Covid-19) has caused various problems in Indonesia. In addition to health issues, Covid-19 has caused economic, social, cultural, security problems, even in the government field. The problem that arises in the field of government that is related to government administration, especially regarding the relations between the central government and regional governments in dealing with the situation of the spread of Covid-19 is associated with decentralized health affairs. The situation of the central government's lack of responsiveness in responding to Covid-19 that has entered Indonesia, which is marked by the emergence of a lot of confusing news, both from the central government and regional governments, has led to various negative actions, chaos even distrust of the community. With these conditions, local governments have an important role in dealing with the Covid-19 outbreak. The raising question will be how are the policies of the regional government in handling this epidemic, but still in line with the instructions of the central government. Local governments and communities have a very vital role in minimizing and handling the spread of the Covid-19 outbreak compared to the central government. There are some shreds of evidence from regions with the red zones areas.Keywords: covid-19 outbreak; local government role; society; policies.